TEACHING METHODOLOGY OF THE LLOYD'S MIRROR INTERFERENCE EXPERIMENT USING A He–Ne LASER - Akimova, Jumakhan Orazbayevna; Orazimbetova, Kalzhamal Oralbaevna (SCIENCE and SOCIETY, 2026)
This article provides an in-depth study of one of the important optical phenomena proving the wave nature of light, the Lloyd interference experiment, using a He-Ne laser. The article provides a detailed description of the theoretical foundations of the interference phenomenon, the physical essence of Lloyd's experiment, the operating principle of the He-Ne laser, the experimental device and methodology, mathematical expressions, measurement results, and error analysis. The experimental results practically confirm the wave properties of light and demonstrate that laser beams are highly coherent.
Keywords: interference; Lloyd's experiment; He-Ne laser; coherent source; wave nature of light.